The Effect of Factors Causes Preeclampsia Towards Left Ventricle Mass Index on Preeclampsia Patient in Undata Regional Hospital of Palu: Pengaruh Faktor-Faktor Penyebab Preeklampsia terhadap Indeks Massa Ventrikel Kiri pada Pasien Preeklampsia di RSUD Undata Palu - Dilladini Nurul Ayu; Tahir Abdullah; Syamsiar S Russeng; Venice Chairiadi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2023)
Background: Preeclampsia is an idiopathic multisystem disorder specific to pregnancy and the puerperium in which multiorgan abnormalities occur in at-risk pregnancies resulting in hypertension and multiorgan dysfunction in the form of an increase in left ventricular mass index which leads to diastolic heart failure. Aim: Determine the relationship the effect of factors causes preeclampsia towards left ventricle mass index on preeclampsia patient in Undata Regional Hospital of Palu Methods: This study used a cross sectional research approach. These variables are measured by research instruments where data can be analyzed according to statistical procedures. Results: From total sample, there were pregnant women of abnormal age 37.67 years (27.3%) and normal age 28.12 years (72.7%) with a mean age of 30.73 ± 5.89 years with history preeclampsia. There were 21 patients (95.5%) with previous obesity and 1 patient (4.5%) had no history of obesity, 14 patients (63.6%) with a history of primigravida and 8 patients with multigravida (36.4%). One patient with multiple pregnancies (4.5%) and 21 patients (95.5% with no history of multiple pregnancies, 3 patients (13.64%) with chronic disease and 19 patients (86 .36%) no history of chronic disease, There are 16 patients (72.7%) patients who use contraception and while 6 patients (27,3%) did not use contraception. Statistical tests risk factors for preeclampsia associated with cardiovascular disease events, hypertension which causes an increase in the Left Ventricle Mass Index (LVMI) it can be seen that in all preeclampsia patients causes uncontrolled hypertension and increase in LVMI above normal values ​​(description according to table), the incidence of preeclampsia with a previous history of preeclampsia 1 (25%) showed a significant relationship with a value of p = 0.001. Conclusion: Factors that cause significant preeclampsia, pregnant women who have a history of preeclampsia and who have a history of multiple pregnancies affect the occurrence of hypertension and an increase in left ventricular mass index.